Employees’ Entrepreneurial Work and Intention to Become Independent Entrepreneurs: A Comparison of India and Slovenia - Swaroop, Sahana (Naše gospodarstvo/Our economy, 2023)
Employees' different levels of entrepreneurial work are likely to be associated with varying levels of knowledge and intentions in a country. This leads the current paper to argue how entrepreneurial work by employees influences employees' approach to running their businesses in India and Slovenia. Random samples of employees in India and Slovenia were surveyed from 2012 to 2019 by Global Entrepreneurship Monitor. The current study emphasized the significant role of entrepreneurial work by employees in their potential to become independent entrepreneurs, albeit with differences between India and Slovenia. Our main theoretical contribution is bridging the gap between dynamic capability and entrepreneurial work by employees at the macro level in India and Slovenia. Additionally, the study provides practical suggestions for Indian policymakers and Slovenian owners/managers